Case Report: Canine Strain– and Study Condition–Dependent Formation of Renaut Bodies in Sciatic Nerves of Beagle Dogs. (January 2020) - Weber, Klaus; Weber, Felix; Longo, Monica; Okazaki, Yoshimasa; Warfving, Nils; Pardo, Ingrid D.; Bolon, Brad; Krinke, Georg J.
Two beagle dog strains were used in a 14-day intrathecal infusion study for a small molecule test article. A moderate number of Renaut bodies (RBs) were observed in the sciatic nerves of control and test article–treated adult animals as early as 1 day after test article infusion (ie, 5 days after catheter implantation in the lumbar cistern). In most cases, the sciatic nerve was affected unilaterally, apparently in association with extended lateral recumbency on one side. The lighter beagle strain (Marshall), and especially the females (which weighed less than age-matched Marshall males), developed more RBs. In contrast, neither females nor males of the larger strain (Harlan) developed any nerve lesions. These data support the hypothesis that RBs develop following mechanical stress to sciatic nerves, suggest that this change may develop fairly quickly following an insult, and demonstrate that different dog strains exhibit strain-specific nerve changes.